Effects of microplastics and lead exposure on gut oxidative stress and intestinal inflammation in common carp (Cyprinus carpio L.). (15th June 2023) - Hu, Yiwei; Lin, Sihan; Tang, Jinglan; Li, Yuxin; Wang, Xiangyi; Jiang, Yusha; Zhang, He; Wang, Binliang
Abstract: Microplastics (MPs) are increasingly being detected in freshwater environments, which have the potential to cause combined toxicity with other contaminants on aquatic organisms. To reveal the ecological risks, the combined effects of lead (Pb) and polyvinyl chloride microplastics (MPs) were explored in the gut of common carp ( Cyprinus carpio L . ). The results confirmed that exposure of Pb alone accelerated Pb accumulation, increased oxidative stress, and activated the inflammation response of the gut. However, the aforementioned effects all decreased under the co-exposure of Pb and MPs. In addition, MPs altered intestinal microbial community of common carp, especially the abundance of immune system-related species. All measured variables were organized for partial least square path modeling, which revealed the combined effects of Pb and MPs on inflammation response. The results implied that MPs reduced inflammation response in two ways, including the reduction of intestinal Pb accumulation and the alteration of the intestinal microbial community. Overall, this study provides a novel aspect of ecological effects on aquatic animals from Pb and MPs exposure. The interesting results remind us that when exploring the ecological risks of MPs, combined effects from other toxic substances must be considered simultaneously. Graphical abstract: Image 1 Highlights: Pb exposure caused more severe gut oxidative stress and inflammation responses compared to MPs. MPs reduced carp Pb accumulation in the gut under Pb-polluted conditions. MPs reduced intestinal inflammation responses under Pb-polluted conditions.